FOXM1 coming of age: time for translation into clinical benefits? - Teh, Muy-Teck (Frontiers in Oncology, 2012)
A decade since the first evidence implicating the cell cycle transcription factor FOXM1 in human tumourigenesis, a slew of subsequent studies revealed an oncogenic role of FOXM1 in the majority of human cancers including oral, nasopharynx, oropharynx, oesophagus, breast, ovary, prostate, lung, liver, pancreas, kidney, colon, brain, cervix, thyroid, bladder, uterus, testis, stomach, skin and blood. Its aberrant upregulation in almost all different cancer types suggests a fundamental role for FOXM1 in tumourigenesis. Its dose-dependent expression pattern correlated well with tumour progression starting from cancer predisposition and initiation, early premalignancy and progression, to metastatic invasion. In addition, emerging studies have demonstrated a causal link between FOXM1 and chemotherapeutic drug resistance. Despite the well-established multifaceted roles for FOXM1 in all stages of oncogenesis, its translation into clinical benefit is yet to materialise. In this contribution, I reviewed and discussed how our current knowledge on the oncogenic mechanisms of FOXM1 could be exploited for clinical use as biomarker for risk prediction, early cancer screening, molecular diagnostics/prognostics and/or companion diagnostics for pers